2016
DOI: 10.1111/micc.12273
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Vascular Remodeling and Leakiness are Important Components of the Pathobiology of Re‐bleeding in Hemophilic Joints: Two Informative Cases

Abstract: Vascular remodeling contributes to perpetuated hemophilic joint bleeding and therefore contributes to progressive arthropathy. Intra-articular or systemic administration of anti-angiogenic drugs, such as vascular endothelial growth factor antagonists, might be of benefit in such patients, but requires study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 21 publications
(24 reference statements)
0
36
0
Order By: Relevance
“…Hemarthrosis in FVIII‐deficient mice leads to synovial neovascularization and associated vascular permeability, followed by formation of large, irregular vessels with increased α‐smooth muscle actin (αSMA) expression . The findings in mice align with patient case studies . Synovial vascular changes may be fueled by upregulation of pro‐angiogenic factors, such as vascular endothelial growth factor, matrix metalloproteinase (MMP)‐9, and stromal‐derived factor‐1, and inflammatory responses to hemarthrosis, including macrophage infiltration and upregulation of proinflammatory cytokines (interleukin (IL)‐1β, IL‐6, and tumor necrosis factor‐α) .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Hemarthrosis in FVIII‐deficient mice leads to synovial neovascularization and associated vascular permeability, followed by formation of large, irregular vessels with increased α‐smooth muscle actin (αSMA) expression . The findings in mice align with patient case studies . Synovial vascular changes may be fueled by upregulation of pro‐angiogenic factors, such as vascular endothelial growth factor, matrix metalloproteinase (MMP)‐9, and stromal‐derived factor‐1, and inflammatory responses to hemarthrosis, including macrophage infiltration and upregulation of proinflammatory cytokines (interleukin (IL)‐1β, IL‐6, and tumor necrosis factor‐α) .…”
Section: Introductionmentioning
confidence: 68%
“…Accumulating evidence suggests that vascular remodeling and instability in association with hemarthrosis may perpetuate joint bleeding events in hemophilia, promoting target joint formation and arthropathic progression . Previously, we have shown that joint bleeding in FVIII‐deficient mice induces temporary inflammation, neovascularization, and vessel permeability, succeeded by vascular remodeling and tissue repair processes .…”
Section: Discussionmentioning
confidence: 89%
“…10 Hence, individual prophylactic therapy with ultrasound monitoring may benefit medical resources allocation, particularly in developing countries such as China. As is known to many, subclinical joint bleeding could not be ruled out in the absence of baseline joint examination with MSKUS, due to aberrant neoangiogenesis and vascular remodelling of the affected joint.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of power Doppler signals reveals abnormal synovial or soft tissue microperfusion, which is a hallmark of synovial inflammation in rheumatoid arthritis . Unique to hemophilic arthropathy, positive power Doppler signals also indicate vascular remodeling associated with leaky vessels and bleeding tendencies . Therefore, it is important to capture the extent of power Doppler signal abnormalities during musculoskeletal US examinations of hemophilic joints.…”
Section: Discussionmentioning
confidence: 99%